Unveiling the Green Revolution: Exploring Green HRM Implementation in Indonesian Enterprises - Handayani, Alfinia Salma; Febriyani, Aulia Kusuma; Darmastuti, Ismi (LifeSciFi, 2024)
Research on the results of using Green Human Resource Management (GHRM) has emerged as a key area of interest for HRM practices in contemporary businesses, some of which are starting to emerge in Indonesia. This research makes use of the PRISMA paradigm in a Systematic Literature Review approach. This study aims to give a thorough overview of recent research on GHRM implementation, including new concerns, operational procedures and policies that are required, the results of GHRM implementation, and suggestions for additional research on the subject of GHRM's effects in Indonesian businesses. The results of this study show that, despite laws imposed by the Indonesian government mandating businesses to manage their environmental impact, there is still a dearth of research on GHRM in Indonesia, which prevents many Indonesian businesses from implementing GHRM practices. Green performance management, green pay and incentive systems, green training and development, and green recruiting and selection are some of the ways that GHRM practices can be implemented. The success of implementing Green Human Resource Management (GHRM) is significantly impacted by various factors such as organizational commitment, the socialization of GHRM programs, environmental education, employee empowerment, and the company's physical environment.